Orbital inflammatory disease following mRNA SARS‐CoV‐2 vaccine. Issue 6 (7th June 2022) - Grunenwald, Solange; Lethellier, Gabriel; Imbert, Philippe; Dekeister, Céline; Caron, Philippe
Abstract: A 65‐year‐old woman reported orbital symptoms two days after her first dose and presented exacerbation of signs after the second dose of BNT162b2 mRNA vaccine. The temporal relationship between the COVID‐19 vaccination and orbital symptoms suggests a probable link between SARS‐CoV‐2 mRNA vaccine and this orbital inflammatory disease. Abstract : We report the first case of orbital inflammatory disease following mRNA SARS‐CoV‐2 vaccination.